SYNAGOGUES OF HALYCH: HISTORY AND ARCHITECTURE - KOZELKIVSKYi, Volodymyr; CHEMERYNSKYI, Andriy (Halych. Scientific work collection, 2023)
The article is devoted to the study of the sacred buildings of Halych in the context of the history of the local Jewish community. Attention is focused on synagogues and beit midrash, which have survived to this day in in different forms. On the basis of archival files and foreign sources, the history of the buildings in the second half of the 18th – beginning of the 21st centuries is described step by step. A description of the external and internal appearance of the buildings was made. A detailed list of inventory that was destroyed during the Great War (1914–1918) is provided. Special attention was paid to the reconstruction and change of the primary functions of sacred buildings during the period of the Ukrainian SSR and independent Ukraine. The publication introduces into scientific circulation little(known cartographic and iconographic materials regarding the localization, description of synagogues and beit midrash. Statistical data on the number of Jews in the structure of the city’s population during 1868–1942 are presented based on the development of governmental and religious schematisms. Historical information about the Halych Jewish community in the first half of the 15th – mid-20th centuries is given. The names of the spiritual and public mentors of the Jewish community in the city are mentioned, and their job duties are described.